PERAN BUDAYA ORGANISASI MEMODERASI PENGARUH KOMITMEN ORGANISASIONAL DAN KOMPETENSI PEDAGOGIK TERHADAP KINERJA GURU (Studi Kasus Pada SMA Negeri Di Kecamatan Pati Kabupaten Pati) (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aimed to examine the influence of organizational commitment and pedagogical competence of the teacher's performance of Public Senior High School with moderation organizational culture. The specific objective of this study is to examine the role of organizational culture moderate the influence of organizational commitment and pedagogical competence of the teacher's performance. The usefulness of this study is to clarify and extend previous study on the role of organizational culture moderate the influence of organizational commitment and pedagogical competence of the teacher's performance. This study used a population of high school teachers in Pati district, Pati regency were 116 teachers. Sampling techniques in this study is non-probability sampling with purposive sampling method. The analysis technique used is the regression model of quasi moderation. Based on the results of the study, the writer can summarize as follows: the organizational commitment does not infuent the performance of teachers, the pedagogic competence influences on teacher performance, the organizational culture influences the performance of teachers, the organizational culture strengthen the influence of organizational commitment to teacher’s performance, the organizational culture strengthen the influence of pedagogical competence on teacher’s performance.Keywords: Organizational Ccommitment, Pedagogical Competence, Organizational Culture and Teacher’s Performance